Use of in vitro bioassays to facilitate read-across assessment of nitrogen substituted heterocycle analogues of polycyclic aromatic hydrocarbons. (September 2019) - Coulet, Myriam; Latado, Hélia; Moser, Mireille; Besselink, Harrie; Tate, Matthew; Minetto, Fanny; Cottet Fontannaz, Claudine; Serrant, Patrick; Mollergues, Julie; Piguet, Dominique; Schilter, Benoît; Marin-Kuan, Maricel
Abstract: Nitrogen-containing polycyclic aromatic hydrocarbons (PANHs or azaarenes) are compounds structurally similar to PAHs (carbon substituted by a nitrogen) reported to occur at low levels in food. Although limited, literature may suggest possible higher toxicity than for PAHs. Using a battery of in vitro assays, the toxicological properties of uncharacterized PANHs of increasing ring number were compared to those of characterized structural PAH analogues. The parameters measured covered key events relevant to the AOP developed for Benzo(a)pyrene: AhR activation, mutagenicity and DNA-damage with and without metabolic activation and endocrine receptors activation/inhibition. There was a strong correlation between the chemical structure and the biological activities of the compounds. AhR activation was the most sensitive parameter with a direct correlation between potency and ring number. The most potent genotoxic chemicals were found amongst the ones with the highest number of ring, and under metabolic activation. Such an approach allowed designing sub-groups based on biological properties in addition to structural similarities. Within a sub-group, toxicological data of tested chemicals may be used to characterize hazard of biologically similar but toxicologically uncharacterized substances. This indicates that in addition to structural properties, in vitro biological data may be useful to conduct read-across. Highlights: The toxicological properties of uncharacterized PANHs were compared to those of characterized structural PAH analogues. An approach using both chemical structure considerations with biological profiling using in vitro bioassays was applied. A battery of in vitro bioassays included AhR activation, mutagenicity/DNA damage and endocrine receptors activation/ inhibition. Such an approach allowed designing sub-groups based on biological properties in addition to structural similarities. Hazard of biologically similar but toxicologically uncharacterized substances maybe done based on characterized chemicals.